2018
DOI: 10.1007/s11336-018-9627-8
|View full text |Cite
|
Sign up to set email alerts
|

Higher-Order Asymptotics and Its Application to Testing the Equality of the Examinee Ability Over Two Sets of Items

Abstract: In educational and psychological measurement, researchers and/or practitioners are often interested in examining whether the ability of an examinee is the same over two sets of items. Such problems can arise in measurement of change, detection of cheating on unproctored tests, erasure analysis, detection of item preknowledge, etc. Traditional frequentist approaches that are used in such problems include the Wald test, the likelihood ratio test, and the score test (e.g., Fischer, Appl Psychol Meas 27:3-26, 2003… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Because the null and alternative hypotheses underlying the SLR statistic are not simple hypotheses, the SLR statistic cannot be expected to be the most powerful statistic for detecting preknowledge on a known set of compromised items, even though the statistic is based on a likelihood ratio. However, Sinharay (2017c), Sinharay (2017d), Sinharay and Jensen (2019), and Wang et al (2019) found the SLR statistic to be as powerful as or more powerful than the existing statistics in detecting item preknowledge and found the Type I error rate of the statistic to be very close to the nominal level. Specifically, Sinharay (2017d) proved the performance of the SLR statistic to be very similar to that of the posterior shift statistic that was found to be the most powerful among eight preknowledge-detection statistics by Belov (2016).…”
Section: Stated Thatmentioning
confidence: 98%
“…Because the null and alternative hypotheses underlying the SLR statistic are not simple hypotheses, the SLR statistic cannot be expected to be the most powerful statistic for detecting preknowledge on a known set of compromised items, even though the statistic is based on a likelihood ratio. However, Sinharay (2017c), Sinharay (2017d), Sinharay and Jensen (2019), and Wang et al (2019) found the SLR statistic to be as powerful as or more powerful than the existing statistics in detecting item preknowledge and found the Type I error rate of the statistic to be very close to the nominal level. Specifically, Sinharay (2017d) proved the performance of the SLR statistic to be very similar to that of the posterior shift statistic that was found to be the most powerful among eight preknowledge-detection statistics by Belov (2016).…”
Section: Stated Thatmentioning
confidence: 98%
“…A large value of L S leads to the rejection of the null hypothesis. Sinharay (2017aSinharay ( , 2017b and Wang et al (2019) demonstrated using real and simulated data that the performance of L S was satisfactory compared to that of several existing statistics for detecting item preknowledge, and Sinharay and Jensen (2019) found L S to have satisfactory Type I error rates and power in several applications of score differencing. Therefore, L S is the only frequentist statistic for score differencing that is considered in this article.…”
Section: A Frequentist Approach To Score Differencingmentioning
confidence: 88%
“…The source of the data set is Cizek and Wollack (2017, p. 14). Researchers such as Sinharay (2017a), Jensen (2019), andZopluoglu (2017) analyzed the same data set to detect various types of test fraud. The test form comprises 170 operational items that are dichotomously scored.…”
Section: Datamentioning
confidence: 99%
See 2 more Smart Citations